Distributors Segments of the Division of Surgical Materials: an application of multivariate analysis - Gouvêa, Maria Aparecida; Plata, Juan Pablo França de la (Review of Business Management, 2007)
This study focused on the analysis of segments of distributors in the category of surgical products in Brazil that are served by a big company that operates in this sector of activity. The information about gross profit, gross sales, credit classification, regional area and region has been considered. The statistical techniques to the definition of segments and their profiles were cluster analysis and multiple correspondences. Models of Lambin (2000) and Czinkota et al. (2001) have been utilized as reference for the development of the segmentation of surgical material market. It was observed that it is possible classifying through cluster analysis the segments of distributors according to differentiated profiles of gross sales and gross profit. The multiple correspondence analyses provided a mapping that presented the association of ranges of gross sales and gross profit with Brazilian regions and with credit classifications which were defined through the historic evolution of the clients. The results of this study can be useful as a source of information to the identification of strategic actions regarding the discount politics of the prices of the products that are offered to the focused on market. Key-words: Segmentation. Surgical material. Multivariate analysis.